Analisis pengaruh perbedaan antara laba akuntansi dengan laba fiskal pada perusahaan dagang terhadap pertumbuhan laba, akrual dan harga saham - Nataherwin Nataherwin (Jurnal Akuntansi, 2013)
This study investigates the role of book-tax differences in indicating the growth of earnings, accruals and investor expectation that reflected in stock price for one period ahead earnings. The methods of research that used in is pooled regression and the technic that used in is purposive sampling, i.e. the choice of sample is being selected by researcher. Using the earnings data of 26 (twenty six) trading companies from the year 2004-2007, the results showed that firm years with large positive (negative) book-tax differences (book income in excess of taxable income) have earnings that are higher than firm years with small book-taxes differences. Furthermore, there are no effect between accruals and investor expectation that reflected in stock price with one period ahead earnings. This study has limitations. One of its is the number of sample is relative short and the sample is not random. The other is the period of study is relative short, only 4 years.